AN ANALYSIS OF CHARACTHERS’ UTTERANCES IN “EPEN CUPEN” INDONESIAN TELEVISION - Zainuddin Zainuddin (English Education : English Journal for Teaching and Learning, 2016)
The research is intended to get public and television viewrs’ English linguistical understanding towards the characters’ utterance on Epen Cupen, one of the entertainment programs in Indonesian Television program. There is one episode of Epen Cupen program is the research data.Finally, the research is done through qualitative research by using document study and where the future collected data are the characters’ utterances in the from of words, pharses andsentences. The data of research are analyzed by contented through qualitative research, Gay Airasian stated: “ qualitative approach is based on collection data and analysis of no numerical data such as observation, intervies,and other more discursive sources of information, ”1 Based on the method, this research used descriptive method.The observation would be instrument of research data collection. In  this case, the researcher would keep him self watching Epen Cupen, that is an ncomedy entertaiment program in Indonesian television. Then , the data are analysed by content based and lingustical unit approach. Here is the table of language analysis from Epen Cupen program